A mixed valence zinc dithiolene system with spectator metal and reactor ligands. (16th August 2016) - Ratvasky, Stephen C.; Mogesa, Benjamin; van Stipdonk, Michael J.; Basu, Partha
Graphical abstract: Crystallographically characterized bis-dithiolene Zn complexes with ligands of differing oxidation states exhibit low energy ligand to ligand (LLCT) charge transfer band. Abstract: Neutral complexes of zinc with N, N′-diisopropylpiperazine-2, 3-dithione ( i Pr2 Dt 0 ) and N, N′-dimethylpiperazine-2, 3-dithione (Me2 Dt 0 ) with chloride or maleonitriledithiolate (mnt 2 − ) as coligands have been synthesized and characterized. The molecular structures of these zinc complexes have been determined using single crystal X-ray diffractometry. Complexes recrystallize in monoclinic P type systems with zinc adopting a distorted tetrahedral geometry. Two zinc complexes with mixed-valence dithiolene ligands exhibit ligand-to-ligand charge transfer bands. Optimized geometries, molecular vibrations and electronic structures of charge-transfer complexes were calculated using density functional theory (B3LYP/6-311G+(d, p) level). Redox orbitals are shown to be almost exclusively ligand in nature, with a HOMO based heavily on the electron-rich maleonitriledithiolate ligand, and a LUMO comprised mostly of the electron-deficient dithione ligand. Charge transfer is thus believed to proceed from dithiolate HOMO to dithione LUMO, showing ligand-to-ligand redox interplay across a d 10 metal.